Clinical effect of endovascular repair of complex aortic lesions using optimized Octopus surgery - Sun, Yanfeng; Zhang, Yang; Sun, Xiwei; Yin, Hang; Wang, Shuai; Li, Xiao; Wang, Zhongying; Luo, Sean X.; Cheng, Zhihua (Frontiers in Bioengineering and Biotechnology, 2023)
Objective: Complex aortic lesions, especially those involving branches of the visceral artery, remain a challenge to treat. A single-center study using the Octopus technique to evaluate the safety and short-term effects of endovascular repair of complex aortic lesions was reported and documented.The data of six cases who underwent Octopus surgery in our center from August 2020 to February 2022 were analyzed retrospectively. The choice of operation scheme, operation time, operation complications, and follow-up data was analyzed among them.The average age of the six patients undergoing Octopus surgery was 55.1 ± 17.2 years. Two cases were diagnosed as pararenal aortic aneurysms; four cases were aortic dissection involving the visceral artery. All cases achieved technical success; all visceral arteries were reconstructed as planned.A total of 17 visceral arteries were planned to be reconstructed; five celiac arteries were embolized. Three cases of gutter endoleak were found during the operation without embolization but with follow-up observation. There were two cases of slight damage to renal function and two cases of perioperative death. Other complications, such as intestinal ischemia and spinal cord ischemia, did not occur. Follow-up ranged from 6 months to 30 months. One patient died of gastrointestinal bleeding six months after the operation. At the six months follow-up, computed tomographic angiography showed that all internal leaks had disappeared. The patency rate of the visceral artery was 100%, and no complications, such as stent displacement and occlusion, occurred during the follow-up period.With fenestrated and branched stent grafts technology not widely available, and off label use not a viable option. Octopus technology for treating complex aortic lesions should be considered. The Octopus technique is an up-and-coming surgical method, but we should recognize its operation difficulty, operation-related complications, and long-term prognosis. We should pay attention to and continue to optimize Octopus technology.